Determinants That Influence The Anxiety Of Pregnant Mothers In Receiving The Covid-19 Vaccine In Puskesmas Nanga Pinoh : Determinants That Influence The Anxiety Of Pregnant Mothers In Receiving The Covid-19 Vaccine In Puskesmas Nanga Pinoh - Rosalina eta (Journal of Health (JoH), 2023)
ABSTRACT Background: Death due to the Covid-19 virus is the main topic and the most serious priority problem for humans today. The government began to think about a safe and effective vaccine strategy and immediately launched a global vaccination program. Pregnant women are a vulnerable group and are at high risk for transmission of Covid-19, because infection with the Covid-19 virus in pregnant women can result in death, premature birth, postpartum hemorrhage and other complications. Research Methods: The design of this research is quantitative research. Types of Correlation Analytical method. with exclusion criteria 12 weeks-32 weeks 6 days healthy condition free of disease complications, came to the health center to conduct an examination at KIA. this study uses a cross sectional approach. Results : Based on the characteristics of respondents aged > 35 years, housewives, college education, and second trimester pregnancy. the economic status of the respondents from prosperous families two to three plus prosperous families totaling 64 respondents experienced mild to moderate anxiety. The level of knowledge of respondents who understand until the application experiences mild to moderate anxiety is 31 respondents. In health workers information, the most respondents were those who received information indirectly, amounting to 55 respondents. Conclusion: from the results of the study it was concluded that the economic status, level of knowledge and information of health workers had a significant influence on the anxiety of pregnant women in receiving the Covid-19 vaccine. Keywords: Covid-19 Vaccine,Pregnant mother, Anxiety